A progressive approach for cross-browser web data generation. (1st January 2014) - Zhu, Jin; Urano, Yoshiyori; Nakazato, Hidenori; Jin, Qun
A layout engine combines markup language (HTML, etc.) with formatting information (CSS, etc.), and displays the combined contents on the screen. It is commonly used for many existing web development applications and web browsers. Especially, web development applications use layout engine to confirm the impact on the layout of web editing results to achieve what you see is what you get (WYSIWYG). At present, different layout engines are adopted by various web development applications and web browsers. As there is not a uniform algorithm adopted by layout engine, the results displayed by web development applications are not necessarily consistent with the display on the web browsers. In addition, the results displayed by web development applications depend on layout engines. Hence, it is difficult to edit the common web contents since it cannot objectively reflect the result on web browsers. In this paper, we propose a progressive WYSIWYG solution, by completely separating web layout design from web data editing to generate cross-browser web data. Our proposed approach does not use layout engine, and thus can avoid the disadvantages mentioned above.